Peripheral artery disease: the new frontiers of imaging techniques to evaluate the evolution of regenerative medicine. (3rd July 2019) - Miceli, Marco; Baldi, Dario; Cavaliere, Carlo; Soricelli, Andrea; Salvatore, Marco; Napoli, Claudio
ABSTRACT: Introduction : Stem cells (ESC, iPSC, MSC) are known to have intrinsic regenerative properties. In the last decades numerous findings have favored the development of innovative therapeutic protocols based on the use of stem cells (Regenerative Medicine/Cell Therapy) for the treatment of numerous diseases including PAD, with promising results in preclinical studies. So far, several clinical studies have shown a general improvement of the patient's clinical outcome, however they possess many critical issues caused by the non-randomized design of the limited number of patients examined, the type cells to be used, their dosage, the short duration of treatment and also their delivery strategy. Areas covered : In this context, the use of the most advanced molecular imaging techniques will allow the visualization of very important physio-pathological processes otherwise invisible with conventional techniques, such as angiogenesis, also providing important structural and functional data. Expert opinion : The new frontier of cell therapy applied to PAD, potentially able to stop or even the process that causes the disease, with particular emphasis on the clinical aspects that different types of cells involve and on the use of more innovative molecular imaging techniques now available.